Multi-dimensional parametric assessment with IoT in acquaintance of digital pipeline - N. Suresh Kumar; Mallikharjuna Rao K; Mahesh Kothuru; Y. Narasimha Rao (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In IoT researches are found millions of devices are connected in global digital infrastructure framed in network fashion. Most of the things on the network use cloud or central database to share their data and control signals to control and manage the devices on the IoT network. Devices on the network need fast traversing paths, to take correct decision in right time. The data synchronization between source and destination is very important in real time parameter maintenance. The multidimensional parametric evaluation of the environment or the surrounding area is facing problems with data synchronization and congestion in the sensor network. This will lead arrival of fault data at the destination. The fault data also leads a misconception at user end. In the present work pipeline integration is proposed to overcome the misconception and synchronization failures. The pipeline and Arduino UNO processor are integrated on Proteus simulation tool. Transducer nodes and the functionalities are analysed with pipeline.